1986
DOI: 10.1136/bjo.70.6.435
|View full text |Cite
|
Sign up to set email alerts
|

Oral acyclovir (Zovirax) in herpes simplex dendritic corneal ulceration.

Abstract: SUMMARY Sixty patients with simple dendritic corneal ulceration were randomly assigned to double blind treatment with either acyclovir tablets (400 mg) or acyclovir ophthalmic ointment administered five times daily. There was no significant difference in the proportions of patients healed in either treatment group (88.9% on oral acyclovir and 96.6% on acyclovir ointment). The median healing time was five days in both groups. No systemic or significant local side effects were noted in either treatment group. Tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0
2

Year Published

1989
1989
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(26 citation statements)
references
References 15 publications
2
22
0
2
Order By: Relevance
“…16 Topical acyclovir 3% ointment is more effective and better tolerated than idoxuridine, vidarabine, and trifluridine; [17][18][19] it is commonly used in Europe for the treatment of HSK. Although acyclovir can be prescribed in the US for oral and dermatological administration, no ophthalmic preparation is available.…”
Section: Acyclovirmentioning
confidence: 99%
“…16 Topical acyclovir 3% ointment is more effective and better tolerated than idoxuridine, vidarabine, and trifluridine; [17][18][19] it is commonly used in Europe for the treatment of HSK. Although acyclovir can be prescribed in the US for oral and dermatological administration, no ophthalmic preparation is available.…”
Section: Acyclovirmentioning
confidence: 99%
“…There was no statistically significant difference in the healing time in patients treated with oral or topical acyclovir [22]. Oral acyclovir is especially useful for treating infants and children with infectious epithelial keratitis because it is difficult to administer topical medications in this age group, and infants and children tend to express a severe immune reaction associated with their epithelial disease [23].…”
Section: Hsv Epithelial Keratitismentioning
confidence: 94%
“…The difference was signifi cantly in favor of the VACV-treated group. Collum et al [1] reported that the total healing times were a mean of 5 and 5.6 days both in oral and topical ACV-treated patients with herpetic dendritic keratitis [4] . However, Porter et al [4] found signifi cantly longer healing times in patients with disciform keratitis treated with either oral or topical ACV (mean 25.9 and 25.3 days, respectively).…”
Section: Discussionmentioning
confidence: 99%
“…Oral ACV has widely been used in the treatment of herpes simplex keratitis and was reported to have a similar effi cacy to topical ACV ointment therapy [1,4] . Oral ACV has also been shown to be effective in the treatment of disciform herpetic keratitis [5] .…”
Section: Discussionmentioning
confidence: 99%